Légendaire acadien de la forêt - Jolicoeur, Catherine (Ethnologies, 1981)
AbstractThe Acadians, like a good number of country folk at one time, spent the winters in the shanties of the Maritimes and Quebec as well as the United States. Amongst lumbermen of diverse origins and temperaments, they acquired experiences which are made concrete as often in their narratives as in their vocabulary. Occasionally these accounts corne together as legends, especially when the feats and gestures of certain lumberjacks bring to mind the memory of those past. The need to moralize, which appears in this genre of narratives, is without doubt one of the aspects which has kept the traditional legend alive.